1992
DOI: 10.1063/1.352073
|View full text |Cite
|
Sign up to set email alerts
|

Variable range hopping in polypyrrole films of a range of conductivities and preparation methods

Abstract: The electronic transport mechanism in polypyrrole is discussed in terms of Mott variable range hopping (VRH) in samples with a wide range of conductivities and which have been formed using different doping techniques. Samples were synthesized in both aqueous and organic media and samples were either doped during polymerization or dedoped afterwards giving a three order of magnitude range of conductivities at 300 K and a range of sample morphologies. No difference in behavior is observed for materials with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
50
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 19 publications
15
50
0
Order By: Relevance
“…The hopping parameters do not follow any systematic change with the supporting electrolyte concentration; however, they are found to satisfy the Mott requirements of ␣R ӷ 1 and W ӷ kT for the variable range hopping mechanism. When compared to the electrical conduction studies in amorphous materials 16,19,20 and pristine PPy and its derivatives, [21][22][23] we observed that the values of the Mott parameters for H-type polysiloxane PPy block copolymers are consistent with the hopping theory and the hopping parameters in the literature. Therefore, we conclude that in the studied temperature range conduction was predominantly provided by the Mott variable range hopping mechanism.…”
Section: Resultssupporting
confidence: 84%
“…The hopping parameters do not follow any systematic change with the supporting electrolyte concentration; however, they are found to satisfy the Mott requirements of ␣R ӷ 1 and W ӷ kT for the variable range hopping mechanism. When compared to the electrical conduction studies in amorphous materials 16,19,20 and pristine PPy and its derivatives, [21][22][23] we observed that the values of the Mott parameters for H-type polysiloxane PPy block copolymers are consistent with the hopping theory and the hopping parameters in the literature. Therefore, we conclude that in the studied temperature range conduction was predominantly provided by the Mott variable range hopping mechanism.…”
Section: Resultssupporting
confidence: 84%
“…͑10͒-͑13͒ and are reported in Table II. It has been assumed 13,19,26,29 that the electron wave function localization length, i.e., ␣ −1 ͑r p ͒ is equal to the width of poly͑o-methoxyaniline͒ monomer unit, i.e., ϳ5.995 Å, 24 since the electrons are always at least delocalized to the extent of the -orbitals on the monomer units. This parameter yields the density of states at the Fermi level; ͓N͑E F ͔͒ on the assumption that the wave function localization length remains independent of temperature and conductivity.…”
Section: ͑8͒mentioning
confidence: 99%
“…localization length of the polypyrrole monomer unit about 3Å [42,43]. The higher values of density of states at the Fermi level are found with increase of PPY content.…”
Section: Resultsmentioning
confidence: 62%